2012
DOI: 10.1016/j.bbabio.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and functional properties of Photosystem II light harvesting complexes in eukaryotes

Abstract: Photoautotrophic organisms, the major agent of inorganic carbon fixation into biomass, convert light energy into chemical energy. The first step of photosynthesis consists of the absorption of solar energy by pigments binding protein complexes named photosystems. Within photosystems, a family of proteins called Light Harvesting Complexes (LHC), responsible for light harvesting and energy transfer to reaction centers, has evolved along with eukaryotic organisms. Besides light absorption, these proteins catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 175 publications
2
120
0
1
Order By: Relevance
“…8C) this suggests that the most likely state of LHCSR1 is a homodimer. LHC proteins can be found as trimers (LHCII), monomers (CP29, CP26, and CP24), and dimers (LHCAs) (55)(56)(57). For both the LHC-like proteins involved in NPQ triggering, namely PSBS and LHCSR3 from Chlamydomonas, there have been reports of dimeric organization, although in most conditions, the most abundant form was a monomer (20,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…8C) this suggests that the most likely state of LHCSR1 is a homodimer. LHC proteins can be found as trimers (LHCII), monomers (CP29, CP26, and CP24), and dimers (LHCAs) (55)(56)(57). For both the LHC-like proteins involved in NPQ triggering, namely PSBS and LHCSR3 from Chlamydomonas, there have been reports of dimeric organization, although in most conditions, the most abundant form was a monomer (20,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…After the sequential formation of the monomeric and dimeric PSII core (C2), minor and major LHCII proteins associate to the PSII dimer to form different sized PSII supercomplexes. The minor LHCII proteins (CP24, CP26, and CP29) provide the molecular interface between the PSII core and the LHCII trimers (LHCII-1,2,3) (Ballottari et al, 2012;Kou ril et al, 2012). The PSII supercomplex (C2S2M2) is the major and largest in vivo form of PSII for Arabidopsis.…”
Section: Formation Of Psii Supercomplexes In Higher Plants and The Romentioning
confidence: 99%
“…Additionally, there are loosely bound major LHCII trimers (L) that can interact peripherally with the C2S2M2 supercomplex to form larger complexes. These L trimers migrate between PSII and photosystem I (PSI) (Caffarri et al, 2009;Ballottari et al, 2012;Kou ril et al, 2012;Pan et al, 2013). Knockout and knockdown mutants in Arabidopsis thaliana have been described for the major and minor LHCII genes and showed that the CP24, CP26, and CP29 play critical roles in association of LHCII trimers to the PSII core (reviewed in Ballottari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions, the excess absorbed energy can be transferred from excited chlorophylls in the triplet state ( 3 Chls*) to molecular O 2 and cause the production of harmful reactive oxygen species (ROS). In plants and green algae most of the light is absorbed by membrane proteins of the Light harvesting complex (Lhc) family (Jansson, 1999;Ballottari et al, 2012;Buchel, 2015), which are associated with photosystem I and II (Dekker and Boekema, 2005;Caffarri et al, 2014) and participate in photoprotection (Duffy and Ruban, 2015).…”
mentioning
confidence: 99%